2009
DOI: 10.1007/bf03191178
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine changes lidocaine free concentrations in rat myocardium without affecting heart function measured by echocardiography

Abstract: Lidocaine is a local anaesthetic widely used in regional and epidural anaesthesia. Clonidine a alpha2-adrenergic agonist is an antihypertensive agent, regulating the production of catecholamines (epinephrine and norepinephrine) and added to local anesthetic infusions in order to improve postoperative analgesia. The aim of the study was to investigate the influence of clonidine co-administration on the binding of 14C lidocaine to rat serum and heart tissue protein as well as its pharmacodynamic effects in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…A decrease in the effective analgesic dose of lidocaine could be achieved, avoiding any undesirable effects on the cardiovascular system. An ultrasound study of the heart has recently proved that there are no statistically significant pharmacodynamic alterations when clonidine is co-administered with lidocaine, in terms of heart function parameters (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the effective analgesic dose of lidocaine could be achieved, avoiding any undesirable effects on the cardiovascular system. An ultrasound study of the heart has recently proved that there are no statistically significant pharmacodynamic alterations when clonidine is co-administered with lidocaine, in terms of heart function parameters (18).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that clonidine administration influences the extent of lidocaine binding and enhances free lidocaine in rat serum and heart tissue protein (18).…”
Section: Introductionmentioning
confidence: 98%
“…Probably a displacement process takes place and lidocaine is displaced by clonidine from its binding sites in serum and tissue proteins thereby leading to rise in its free fraction. [59]. Drugs that are documented to be of AAP depended activity are presented in the following table (1)…”
Section: Aag Binding Experimental Studiesmentioning
confidence: 99%